Dust and chemical exposures, and miscarriage risk among women textile workers in Shanghai, China. Issue 3 (19th September 2008) - Wong, E Y; Ray, R M; Gao, D-L; Wernli, K J; Li, W; Fitzgibbons, E D; Camp, J E; Astrakianakis, G; Heagerty, P J; De Roos, A J; Holt, V L; Thomas, D B; et al.
Abstract : Introduction: To investigate possible associations between miscarriage and occupational exposures in the Shanghai textile industry. Methods: A retrospective cohort study of miscarriages among 1752 women in the Shanghai textile industry was conducted. Reproductive history was self-reported by women and occupational work histories were collected from factory personnel records. Occupational exposures were assigned by linking work history information to an industry-specific job-exposure matrix informed by factory-specific textile process information and industrial hygiene assessments. Estimates of cotton dust and endotoxin exposure were also assigned. Odds ratios (OR) and 95% CI were estimated by multivariate logistic regression, with adjustment for age at pregnancy, educational level, smoking status of the woman and her spouse, use of alcohol, and woman's year of birth. Results: An elevation in risk of a spontaneously aborted first pregnancy was associated with exposure to synthetic fibres (OR 1.89, 95% CI 1.20 to 3.00) and mixed synthetic and natural fibres (OR 3.31, 95% CI 1.30 to 8.42). No increased risks were observed for women working with solvents, nor were significant associations observed with quantitative cotton dust or endotoxin exposures. Associations were robust and similar when all pregnancies in a woman's reproductive history were considered. Conclusions: Occupational exposure to synthetic fibres may cause miscarriages, and this possibility should be the subject of further investigation.